Recurrent malignant phyllodes tumor of the breast: A case report. Issue 49 (December 2017) - Wang, Qinqin; Su, Jing; Lei, Yutao
Abstract: Rationale: Phyllodes tumor is a rare fibro epithelial neoplasm of the breast. They resemble fibroadenomas clinically and can be mistakenly ignored sometimes. Patient concerns: We report the case of a young woman with her first presentation to hospital due to a hypoglycemia and she underwent 2 excised fibroadenomas in the same breast before diagnosed of malignant phyllodes tumor. She was complaining about 2 masses presented in her right breast 4 months after mastectomy. Diagnoses: Recurrent phyllodes tumor of the breast. Interventions: We conducted an immediate autologous myocutaneous flap transplantation after a wide-excision. Postoperative radiotherapy was recommended. Outcomes: She was in good general condition without tumor relapses during 8 months of follow-up. Lessons: Recurrent fibroadenomas in the same breast, especially those of large size with rapid growth rate, suggesting a high transformation possibility from fibroadenoma to phyllodes tumor. We recommend an extended tumor resection and immediate or delayed reconstruction of the breast for the recurrent phyllodes tumor with separately multiple relapses.